URGENSI KOMPETENSI KOMUNIKASI ILMIAH PUSTAKAWAN UNTUK PROGRAM PENGEMBANGAN LAYANAN PERPUSTAKAAN - Nashihuddin, Wahid (Association of Indonesian Library and Information Professionals, 2019)
The purposes of this study are to know: (1) the urgencies of librarian?s scholarly communication; (2) competence of librarian's scholarly communication; and (3) library?s scholarly communication programs. The data type of this study is descriptive - qualitative. The data source for this study is a literature review. The study results showed that scholarly communication is a core competency of librarians who could help library service development programs. These core competencies include the ability of librarians to implement the digital literacy and scientific literacy programs in the library, such as user education, publications or research, education or training, focus group discussions, scientific meetings, and research corner services. As a recommendation, the librarian's institutions (especially academic libraries and research institutions) should arrange the librarian's scientific competency development programs